Isogeometric Approximation Methods Using the Interlineation Operators - Sergienko, Ivan; Lytvyn, Oleg M.; Lytvyn, Oleg O.; Tkachenko, Alexandr; Grytsai, Olga (NTU "KhPI", 2016)
Interlineation of functions of two or more variables is approximation of the functions by their traces or traces of some differential operators on the fixed system of lines. The given paper presents the analysis of the building methods of interlineation operators, that preserve the differentiability class and have the same traces as the approximated function.
Keywords: approximation; preservation class; interlineation